The role of muscle mass in endurance performance and neuromuscular fatigue: a systematic review and meta-analysis - Zhang, J.; Pearson, A. Z.; Grunau, M.; Iannetta, D.; Millet, G. Y.; Aboodarda, S. J. (Sports Medicine, 2025)
Background: Numerous physiological factors can contribute to endurance performance. Among them, active muscle mass engaged in an exercise task has been postulated to alter fatigue. Objective: This systematic review and meta-analysis aimed to examine the effect of active muscle mass on endurance performance and neuromuscular fatigue. Methods: PubMed, EMBASE, SPORT Discus, Web of Science, and PsycINFO databases were searched using a combination of terms relating to the intervention (muscle mass) and outcomes. This review was preregistered on PROSPERO (CRD42022304793). Results: A total of 19 studies were included in the qualitative synthesis of the systematic review, with 17 in the meta-analysis. Whereas time-to-task failure was not different between active muscle mass exercises (Hedges` g: 0.39, 95% confidence interval [CI] - 0.39, 1.15, p = 0.317), the decline in maximal force-generating capacity after closed- and open-ended tasks was greater following smaller muscle mass exercise (Hedges` g: - 1.26, 95% CI - 2.0, - 0.50, p = 0.001). The greater decline in maximal force was likely due to a greater deterioration of muscle contractile function (reflected in decreased electrically evoked twitch force) following smaller muscle mass exercise (Hedges` g: - 1.37, 95% CI - 2.34, - 0.44, p = 0.002), with a small contribution from differences in voluntary activation (Hedges` g: - 0.28, 95% CI - 0.73, - 0.03, p = 0.034). Conclusions: Overall, endurance performance was the same in response to small versus large muscle mass exercise, while muscle contractile capacity and voluntary activation were reduced to a greater extent following small muscle mass exercise. Individuals can tolerate greater muscle metabolic perturbations with a smaller amount of active muscle mass.